Assessment of the effects of Annona muricata leaf aqueous extract in vitro - Liliána, Buzogáňová; Martin, Kello; Martina, Bago Pilátová; Ogurčáková, Daniela; Vašková, Janka (Emirates Journal of Food and Agriculture, 2022)
Background: The extracts of Annona muricata, also known as graviola, form part of traditional medicine. Objectives: Verification of their effects and elucidation of their mechanisms is beneficial in terms of the utility of these extracts in treatment or prevention. Methods: We monitored the effectiveness of an extract of dried graviola leaves available for direct consumption on cancer cell lines and isolated rat liver mitochondria. Results: The Jurkat cell line exhibited the highest, sensitivity, with the metabolic activity of cells reaching less than 10% at the highest tested concentration. The effect was dose-dependent. The viability of Jurkat cells was affected after more than the 72 hours. At the same time, there was also a reduction of mitochondrial membrane potential. At 24 to 48 hours incubation, no increase was found in the activity of caspase-3 but increased levels were found for the non-phosphorylated form of Bcl-2. Higher concentrations of graviola affected the mitochondrial redox state by dramatically reducing the levels of reduced glutathione. This was achieved through reduction in the activity of glutathione-S-transferase. Conclusion: Our findings indicate that the studied preparation of graviola displayed cytotoxic effects on some cells, depending on the dose and length of action.